Relationships of stable carbon isotopes, plant water potential and growth: an approach to asses water use efficiency and growth strategies of dry land agroforestry species - Gebrekirstos, Aster; Noordwijk, Meine van; Neufeldt, Henry; Mitlöhner, Ralph (Springer, 2011)
The relationships between annual wood stable carbon isotope composition (δ13C), dry season midday plant water potential, and annual growth rate were investigated to asses the ability of agroforestry species to adapt to climate changes. 6–8 stem disks from four co-occurring species (Acacia senegal, A. seyal, A. tortilis and Balanites aegyptiaca) were collected for radial growth measurements using tree-ring analysis spanning 1930–2003. Annual δ13C was measured on three tree disks per species for the period 1970–2002. Midday plant water potential was measured during the dry season. Annual radial growth and midday plant water potential ranged from 0.27 to 9.12 mm and −1.0 to −5.0 MPa, respectively, with statistically significant differences. After correcting annual wood δ13C for atmospheric changes in δ13C, carbon isotopic composition ranged from −22.22 to −26.58‰. Relationships between δ13C, radial growth and plant water potentials revealed the interaction of water availability, stomatal conductance, δ13C values and growth. Two contrasting water use strategies and competitive advantages can be distinguished. Species with lower mean δ13C values (A. senegal and A. seyal) show high plant water potential and, hence, better growth during moist years. Thus, they indicate low water use efficiency (WUE) and opportunistic water use strategy. On the other hand, species with lower water potentials (A. tortilis and B. aegyptiaca) showed relative better growth performance and less increase in δ13C in drought years, reflecting their high WUE and conservative water use strategy. These results suggest that δ13C in tree rings can be useful in estimating historic changes in plant WUE and hence in screening drought tolerant species in the face of expected climate changes, as well as for assessing the functional diversity and risk reduction in mixed vegetation.